Separation of variables for nonlinear equations of hyperbolic and korteweg-de Vries type - Yuryk, Ivan (My University, 2011)
We propose substitutions that have been used for construction of wide classes of exact solutions with the generalized separation of variables for nonlinear eguations of the hyperbolic and Korteweg-de Vries type (KdV-type). These solutions cannot be obtained by means of S.Lie method or by the method of conditional symmetries.
Keywords: метод Лі; нелінійні гіперболічні рівняння; рівняння Кортевега-де Фріза; узагальнене відокремлення змінних; обобщенное разделение переменных; Нелинейые гиперболические уравнения; уравнения Кортевега-де Фриза; Lie method; Nonlinear hyperbolic equations; Korteweg-de Vries equations; generalized separation of variables; кафедра вищої математики імені проф. Можара В. І.